(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
The reader of this note will find a series of short arguments that summarize the characteristics which can be considered essential to a philologist’s work. The range of typologies and methods of philological approach to literary texts in the vernacular is so wide that its boundaries cannot be easily defined. Moreover, in philology, each case is a case in and of itself that is to be dealt with and solved in specific and particular ways each time; nothing or almost nothing can be generalized. Nevertheless, the function of a philologist, and in particular of a philologist-editor, is always and in any case to provide mediation between the author and the reader.